Development and Challenges: Marriage Laws and the Influence of Technology - Ainun Najib (Innovative: Journal Of Social Science Research, 2023)
In this millennial era, the influence of technology on marriage law presents both development and challenges. It is evident that technology now provides convenience but also brings about various challenges. Therefore, it is important to respond to mitigation efforts to address the rapidly evolving impact of technology on marriage law. This study focuses on how the development and challenges of marriage law concerning the influence of technology and why it is crucial to respond to these developments and challenges. This research used qualitative library research with a descriptive analysis method. The results of this study indicated that: First, the development and legal challenges of marriage are as follows: On one hand, marriage law needs to be adaptive to the changing situations and conditions as a requirement for the practice of marriage in the era of technology. On the other hand, there is a need for the reform of marriage laws to cope with technological advancements in order to facilitate the process of marriage and ensure that it is not in conflict with marriage applications in technological developments. Therefore, marriage laws should align with and be adjusted to the technological advancements that have become part of people's lives. Secondly, it is crucial to implement legal reforms that are in line with technological advancements for the future. This will contribute to providing easy access to various conveniences for the society and prevent the negative impacts and influences of technology on marital affairs in people's lives in a preventive manner.